1964 : eyes of the storm - McCartney, Paul (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2023)
Taken with a 35mm camera by Paul McCartney, these largely unseen photographs capture the explosive period, from the end of 1963 through early 1964, in which The Beatles became an international sensation and changed the course of music history.